Power and kinetic energy in rowing - Kleshnev, V. (BioRow, 2018)
Recently, we had an interesting discussion with Mathijs Hofmijster about power in rowing (full text is here). The point I made is that power measurements and the "Applications of Newton's Laws" (analysis of the power transformation into motion and kinetic energy, which Mathijs tried to do) are two different areas and utilise different methods of analysis. The first area targets how the power is PRODUCED; the second - how it is USED. Here is the author's model of power transformation into kinetic energy in rowing (Fig.1), excluding any mathematics for simplicity.